2019
DOI: 10.16910/jemr.12.6.6
|View full text |Cite
|
Sign up to set email alerts
|

Microsaccades and covert attention: Evidence from a continuous, divided attention task

Abstract: A substantial question in understanding expert behavior is isolating where experts look, and which aspects of their environment they process. While tracking the position of gaze provides some insight into this process, our ability to attend covertly to regions of space other than the current point of fixation, severely limits the diagnostic power of such data. Over the past decade, evidence has emerged suggesting that microscopic eye movements present during periods of fixation may be linked to the spatial dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…It has potential for visual perception [2,164,165]. Microsaccades are small, fast, jerk-like eye movements that occur during voluntary fixational eye movements [164,204,209]. They can serve as a signal for fixation detection algorithms [53] and rotate around the point of fixation with small amplitudes [53].…”
Section: Understanding Of Eye Movementmentioning
confidence: 99%
See 1 more Smart Citation
“…It has potential for visual perception [2,164,165]. Microsaccades are small, fast, jerk-like eye movements that occur during voluntary fixational eye movements [164,204,209]. They can serve as a signal for fixation detection algorithms [53] and rotate around the point of fixation with small amplitudes [53].…”
Section: Understanding Of Eye Movementmentioning
confidence: 99%
“…As the fastest eye movements, saccades have speeds ranging from 30 to 900 degrees per second, influenced by factors such as target distance, amplitude, and individual differences. Saccades play a crucial role in tasks like reading, environmental scanning, and searching objects of interest [47,209]. In human visual systems, these eye movements are driven by the attention mechanisms: bottom-up and topdown, which have formed the basis for different gaze interactive applications.…”
Section: Understanding Of Eye Movementmentioning
confidence: 99%
“…But this line of argument runs into another problem: it now becomes an empirical question whether mental attention exists at all. In the literature, it has been suggested that microsaccades might be required for covert attention shifts (Barnhart et al 2019;Engbert and Kliegl 2003;Hafed and Clark 2002;Rolfs 2009;Ryan, Keane, and Wallis 2019;Yuval-Greenberg, Merriam, and Heeger 2014). In this usage, 'covert attention' does not mean a shift in attention without eye movements, as microsaccades are eye movements, but instead follows Posner's definition of covert attention as 'attention to a position in visual space other than fixation' (Posner 1980, 3).…”
Section: Attending Affordancesmentioning
confidence: 99%